KEWENANGAN PENGADILAN AGAMA DALAM SENGKETA PERBANKAN SYARIAH - Mahir . (Maliyah : Jurnal Hukum Bisnis Islam, 2015)
The existence of Islamic banking system, with the different variant products, has its own legal implications particularly after emerging some disputes for the parties involved. The banking dispute is usually solved through the court. In this position, Court is to be a place to seek justice and resolve legal issues that arise. In addition, there is also an alternative of non-litigation settlement in Indonesia. Undang-undang Perbankan Syariah no 21 tahun 2008, which has provided the competence or authority to public courts in Islamic banking dispute resolution, has reduced the absolute competence of religious courts, in Undang-undang nomor 3 tahun 2006, it is very clearly mentioned that the religious courts have absolute competence in the field of economy of Islam, including the Islamic banking system. The Absolute authority of religious courts as defined in Undang-undang no 3 tahun 2006, in its application, is still potentially determined by choice of forum that can be done by the parties involved in contract